Negative impact of unilateral sanctions on the enjoyment of human rights in the COVID-19 pandemic - Douhan, Alena F. (Journal of the Belarusian State University. International Relations, 2020)
The article is aimed to provide an overview of sanctions imposed by individual states and regional organisations without or beyond the authorisation of the UN Security Council in the course of COVID-19 pandemic and assess their impact on the enjoyment of different categories of human rights, identify the most vulnerable groups of population and efficacy of humanitarian exemptions as well as the availability of delivery of humanitarian aid. The article is based on the materials collected by the UN special rapporteur on the negative impact of unilateral coercive measures on the enjoyment of human rights in the course of preparation of the annual report to the UN General Assembly but reflect a personal academic assessment of the authour and cannot be viewed as the position of the United Nations organs.